Konstruksi Sosial Usahatani Jagung Hibrida Kelompok Tani Mawali Di Desa Matungkas Kecamatan Dimembe Kabupaten Minahasa Utara - Samana, Alda; Jocom, Sherly Gladys; Ngangi, Charles Reijnaldo (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
The social construction of the Mawali farmer group is an individual action. It cannot be denied that the individuals themselves need a group that is able to work together and is able to solve the problems they face. Besides humans as individual beings, humans are also social beings who will continue to interact with each other, both individually and in groups or in groups and in society. Likewise, farmers need their members in a farmer group to be able to solve various agricultural problems such as finding solutions together, being able to interact with fellow members, especially in the process of a farmer group in selecting farming products, implementing and developing their farming business as well as willingness and preparedness. in developing hybrid corn farming. The purpose of this study was to understand the process of forming farmergroups and selecting hybrid corn farming commodities in the Mawali Farmer Group, Matungkas Village, Dimembe District, North Minahasa Regency. The results showed that social construction in the formation of farmer groups with hybrid corn farming in the Mawali farmer group could process well and achieve good goals and be successful in hybrid corn farming which and supported by the addition of farming, namely chili can be seen from externalization, objectivation and internalization.